Bioassay-guided isolation of three new alkaloids from Suillus bovinus and preliminary mechanism against ginseng root rot - Xiong, Miaomiao; Yang, Xiaomin; Yao, Lan; Li, Zhuang; Zhang, Jinxiu; Lv, Jianhua (Frontiers in Microbiology, 2024)
In order to control the occurrence of ginseng root rot caused by Fusarium solani (Mart.) Sacc., the antifungal compounds of the mushroom Suillus bovinus were investigated. And three new alkaloids (1-3), named bovinalkaloid A-C, along with one known analogue (4), were isolated and identified by bioassay-guided isolation and spectroscopic analyses. Compound 1 strongly inhibited the mycelial growth and spore gemination of F. solani with minimum inhibitory concentration of 2.08 mM. Increases in electrical conductivity, nucleic acid, and protein contents, and decreases in lipid content showed that the membrane permeability and integrity were damaged by compound 1. Compound 1 also increased the contents of malondialdehyde and hydrogen peroxide and the activities of antioxidant enzymes, indicating that lipid peroxidation had taken place in F. solani. Compound 1 may serve as a natural alternative to synthetic fungicides for the control of ginseng root rot.